Prediction of the efficiency of physiotherapy treatment of eye pathology according to the data of triplex scanning of eye and orbit vessels - I. P. Shurygina; E. V. Kabardina; I. V. Shlyk; M. K. Shulikova (Кубанский научный медицинский вестник)
In the paper in order to predict the efficiency of physiotherapy treatment of the patients with eye pathology ultrasound Doppler sonography study of the parameters of orbital blood flow before and after 1-2 manipulations was conducted (Russian Federation patent dated 20.11.2007 № 2310389).The ultrasound prognostic criteria suggested in this paper allow to define the strategy of physiotherapy treatment of the patients with eye pathology.